(untitled) (Iranian Journal of Kidney Diseases, 2015)
Introduction. The genetic variations of co-stimulatory molecules can affect the extent of T cell activity during T-cell mediated immunity, especially in transplant patients. This study aimed to investigate the association of programmed cell death 1 (PDCD1) and programmed cell death 1 ligand 1 (PDCD1LG1) gene polymorphisms with clinical outcome of kidney transplantation. Materials and Methods. A total of 122 patients with a kidney transplant were included in this retrospective study. Patients were classified into two groups of biopsy-proven acute allograft rejection (AAR) and stable graft function (SGF) during the 5-year follow-up period. Four single nucleotide polymorphisms in PDCD1 and PDCD1LG1 were determined in the groups of patients as well as in 208 healthy control individuals. Results. The frequencies of PD-1.3 (+7146 G>A), PD-1.9 (+7625 C>T), PD-L1 (8923 A>C), and PD-L1 (+6777 C>G) genotypes and alleles were not significantly different between the AAR and SGF groups. In comparison with healthy controls, PD-1.9 (+7625 C>T) genotype and T allele were significantly more frequent in all of the patients and in those with SGF. Overall, 27 of 122 kidney allograft recipients experienced delayed graft function, and a higher frequency of PD-1.9 (+7625 C>T) genotype and T allele was observed in this group versus those without delayed graft function. Similarly, a significant high frequency of this genotype was found among the AAR subgroup of patients with delayed graft function. Conclusions. Our results indicate that potentially functional genetic variation in PDCD1 can influence the outcome of kidney transplantation.